Identification and determination of myriocin in Isaria cicadae and its allies by LTQ-Orbitrap-HRMS - Wen-ming Cheng; Qun-lin Zhang; Ze-hua Wu; Zhi-yong Zhang; Yi-ru Miao; Fan Peng; Chun-ru Li (Mycology, 2017)
A hybrid linear ion trap-quadrupole-Orbitrap high-resolution mass spectrometry (LTQ-Orbitrap-HRMS) was used to qualitatively and quantitatively analyse the myriocin in Isaria cicadae and its allies. The samples were prepared with 95% methanol for 30 min by ultrasonic-assisted extraction. The target compound was purified by ODS solid-phase extraction (SPE) column. The enriched samples were identified by mass spectrometry. The results showed that the contents of myriocin in both wild and artificial Isaria cicadae were below the detection limit, while a strain of Ophiocordyceps longissima and Cordyceps cicadae Shing (Dujiaolong), both closely related to the Isaria cicadae, and its asexual mycelia are rich in myriocin. It suggests that it may be wrong to consider C. cicadae as I. cicadae’s teleomorph in Genbank or Mycobank in many published reports based on chemical classification, and the species rich in myriocin is probably not Isaria cicadae.